2017
DOI: 10.1037/abn0000286
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pathological narcissism on interpersonal and affective processes in social interactions.

Abstract: Narcissism has significant interpersonal costs, yet little research has examined behavioral and affective patterns characteristic of narcissism in naturalistic settings. Here we studied the effect of narcissistic features on the dynamic processes of interpersonal behavior and affect in daily life. We used interpersonal theory to generate transactional models of social interaction (i.e., linkages among perceptions of others’ behavior, affect, and one’s own behavior) predicted to be characteristic of narcissism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 61 publications
6
90
1
2
Order By: Relevance
“…Such work has yielded results that highlight the importance of contextual factors and the interpersonal behavior of one's interactants (Pincus et al, 2014; Thomas et al, 2014b; Wright et al, 2017; Zuroff et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Such work has yielded results that highlight the importance of contextual factors and the interpersonal behavior of one's interactants (Pincus et al, 2014; Thomas et al, 2014b; Wright et al, 2017; Zuroff et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In support of this viewpoint, Wright et al found that individuals with high levels of grandiose narcissistic traits experience intense negative emotion when perceiving others as dominant in social interactions. Further, grandiose narcissism appears to be related to attempting to promote a ‘perfect’ self‐image to others .…”
Section: The Current Investigationmentioning
confidence: 99%
“…From these we created two subscales corresponding to dominance (Dominance = Dominant -Submissive) and affiliation (Affiliation = Agreeable -Quarrelsome). Prior work has treated the four scales as separate, but we collapsed them based on theoretical grounds, and to reduce number of statistical models/tests, as we have done in our prior work (Wright et al, 2017).…”
Section: Momentary Interpersonal Behavior Of Self and Other The Partmentioning
confidence: 99%
“…As a way to address these limitations, Contemporary Integrative Interpersonal Theory of personality and psychopathology (Hopwood et al, 2019;Wright et al, 2020) provides an ideal framework for studying the shared and distinct contributions of insecure attachment and BPD to impairments in socio-affective functioning. Key to interpersonal theory is the assumption that indiviual differences are reflected in characteristic patterns of affective and behavioral processes arising during social interactions in response to perceived internal (i.e., mental construal) and external (i.e., proximal behavior of others) social cues (Kiesler, 1996;Wright et al, 2017).…”
mentioning
confidence: 99%